An Adverse Outcomes Approach to Study the Effects of SARS-CoV-2 in 3D Organoid Models. Issue 3 (15th February 2022) - Basu, Amrita; Pamreddy, Annapurna; Singh, Pragya; Sharma, Kumar
Graphical abstract: Highlights: COVID-19 studies on traditional in vitro models in 2D and its disadvantages. Importance of 3D models and adverse outcome pathways for multi-organs dysfunction. 3D Organoid studies: Molecular initiating events, key hallmarks followed by AOPs. Role of ACE2 and various molecular pathogenesis in multi-organs failure. The review discusses important findings from all these 3D organoid models. Abstract: The novel SARS-CoV-2 virus outbreak is the major cause of a respiratory disease known as COVID-19. It has caused a global pandemic and has resulted in mortality in millions. The primary mode of infection is respiratory ailments, however, due to multi-organ complications, COVID-19 patients displays a greater mortality numbers. Due to the 3Rs Principle (Refine, Reduce, Replacement), the scientific community has shifted its focus to 3D organoid models rather than testing animal models. 3D organoid models provide a better physiological architecture as it mimics the real tissue microenvironment and is the best platform to recapitulate organs in a dish. Hence, the organoid approach provides a more realistic drug response in comparison to the traditional 2D cellular models, which lack key physiological relevance due to the absence of proper surface topography and cellular interactions. Furthermore, an adverse outcome pathway (AOPs) provides a best fit model to identify various molecular and cellular events during the exposure of SARS-CoV-2. Hence, 3D organoid research provides information related to gene expression, cell behavior, antiviral studies and ACE2 expression in various organs. In this review, we discuss state-of-the-art lung, liver and kidney 3D organoid system utilizing the AOPs to study SARS-CoV-2 molecular pathogenesis. Furthermore, current challenges are discussed for future application of 3D organoid systems for various disease states.